Modified silicon carbon material as well as preparation method and application thereof

By depositing amorphous silicon particles on porous carbon materials and using silicone passivating agent for passivation treatment, the problem of volume expansion and Si-H bonds easily reacting during lithium embedding of silicon carbon materials is solved, and the stability and electrochemical performance of the material are improved.

CN119725507AActive Publication Date: 2025-03-28HUNAN SHINZOOM TECH
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202311266708.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The volume expansion of existing silicon-carbon materials during lithium embedding process leads to material powdering and poor cycle stability, and the Si-H bond of nano-silicon can easily react with oxygen to reduce electrochemical performance.

Method used

By depositing amorphous silicon particles on porous carbon materials and passing through physical or chemical vapor deposition using silicone passivating agent, the hanging bonds and molecular composition on the surface of nano-silicon particles are changed to form a stable passivation layer to isolate oxygen.

Benefits of technology

It improves the cyclic stability and electrochemical properties of silicon-carbon materials, prevents the reaction of Si-H bonds with oxygen, extends battery life and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725507A_ABST
    Figure CN119725507A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of secondary batteries, and particularly relates to a modified silicon carbon material as well as a preparation method and application thereof. The method comprises the following steps: S1, depositing nano silicon on a porous carbon material to obtain a silicon-carbon material; s2, the obtained silicon-carbon material is subjected to passivation treatment through a physical vapor deposition method or a chemical vapor deposition method, a passivating agent used in the passivation process is an organic silicon passivating agent, the general formula of the organic silicon passivating agent is RSiX3 or R2SiX2, and an R group and an X group are not H at the same time. A porous carbon material with a certain pore structure is used as a substrate, nano silicon is deposited in situ in the porous carbon to prepare the novel silicon-carbon material, the surface of the silicon-carbon material is subjected to passivation modification treatment through a silicon-containing substance, and dangling bonds and molecular constitution on the particle surface of the silicon-carbon material are changed; therefore, the modified silicon-carbon material which can stably exist in an air and slurry system and is excellent in processing performance is obtained, and meanwhile, the electrochemical performance of the material is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a modified silicon-carbon material and a preparation method and application thereof. Background Art

[0002] The theoretical specific capacity of silicon is as high as 4200mAh / g, which is more than 10 times that of graphite negative electrode materials. Silicon negative electrode materials have attracted the attention of researchers for their high gram capacity and abundant resources. However, the process of lithium insertion in silicon negative electrode materials is accompanied by a huge volume expansion (~300%), which causes the electrode material to pulverize and separate from the current collector, showing poor cycle stability and poor conductivity, which have become factors restricting its widespread application.

[0003] Most of the existing patents and technologies use methods of in-situ coating of organic carbon sources or direct mixing and doping of inorganic graphite materials. Such processes are not conducive to the expansion and contraction effect of silicon materials, which will cause the material to crack and powder after a period of cycling, resulting in material degradation. In addition, the prior art also discloses some technical solutions for depositing nano-silicon into the pores of porous carbon materials and using the spatial structure of porous carbon materials to limit the expansion of silicon materials. However, in order to ensure that the deposited nano-silicon is amorphous silicon, the temperature used to prepare the silicon-carbon material is not high, so the formed nano-silicon particles will still have Si-H bonds. However, Si-H bonds have strong reactivity and will react with oxygen in the air to generate electrochemically inert silicon dioxide, thereby reducing the gram capacity of silicon-carbon materials; or react with water in the slurry system to generate hydrogen, resulting in poor slurry coating performance, and further chemical reactions inside the battery to cause gas production, seriously affecting the battery life and posing potential dangers. The use of oxygen and other oxidants for passivation not only reacts with the surface of nano-silicon, but the formation of the oxide layer is a dynamic process. As the oxidation proceeds, the oxide layer will gradually thicken, causing the electrochemically inert silicon dioxide layer to gradually thicken, reducing the gram capacity of the silicon-carbon material. The thick oxide layer hinders the transmission of lithium ions and reduces the capacity of nano-silicon. At the same time, the sample will continue to react with oxygen in the air after oxygen treatment. If traditional carbon coating is used, since the deposited nano-silicon is prone to crystallization at high temperatures, resulting in the growth of silicon grain size, the coating formed at a lower coating temperature can isolate the nano-silicon from water to a certain extent, but the isolation effect is not good. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the above-mentioned defects of the silicon-carbon material in the prior art, thereby providing a modified silicon-carbon material and a preparation method and application thereof.

[0005] To this end, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a modified silicon-carbon material, comprising the following steps:

[0007] S1, depositing nano-silicon on a porous carbon material to obtain a silicon-carbon material, wherein the nano-silicon is amorphous silicon and Si-H bonds exist on the surface of the nano-silicon particles;

[0008] S2, passivating the obtained silicon-carbon material by physical vapor deposition or chemical vapor deposition, wherein the passivating agent used in the passivation process is an organic silicon passivating agent,

[0009] The general formula of the organosilicon passivator is RSiX3 or R2SiX2, and the R group and the X group are not H at the same time.

[0010] Optionally, the organosilicon passivator is in liquid state at normal temperature and pressure, with a boiling point of ≤300°C and a cracking temperature of ≤700°C.

[0011] Optionally, in the organosilicon passivator, the R group and the X group are independently selected from at least one of hydrogen, halogen, hydroxyl, alkyl, alkenyl, alkoxy, phenyl, and alkylamine;

[0012] Optionally, the R group and the X group are independently selected from at least one of -H, -Br, CI, -OH, -Cl, -CCH, -CH3, -C2H4, -OCH3, -OC2H6, -C6H5, -OC3H5, and -C3H8N.

[0013] Optionally, the organosilicon passivator includes at least one of tetraethoxysilane, tetramethyl silicate, methyltrichlorosilane, r-aminopropyltriethoxysilane, vinyl silane, and allyloxytrimethylsilane.

[0014] Optionally, in step S2, the temperature of the passivation treatment is 100-800°C, the concentration of the organosilicon passivator in the reactor is 0.01-1 mol / L, and the residence time is 0.1h to 5h;

[0015] Optionally, the temperature of the passivation treatment is 200-700°C.

[0016] Optionally, in step S2, the physical vapor deposition is selected from one of vacuum evaporation, vacuum sputtering, and vacuum ion beam method;

[0017] And / or, in the chemical vapor deposition method, the organosilicon passivator is pre-atomized; the atomization method includes but is not limited to single-phase atomization and medium atomization.

[0018] Optionally, in step S1, silane is used as a silicon source and nano-silicon is deposited by chemical vapor deposition;

[0019] And / or, the temperature of the nano-silicon deposition step is 500-1000° C., and the reaction time is 1-100 h.

[0020] And / or, an inert gas or hydrogen is used as a carrier gas.

[0021] And / or, the porous carbon material has a D50 median particle size of 6-20 μm and a specific surface area of ​​500-2000 m 2 / g, tap density is 0.2-0.6g / cm 3 The pore volume is in the range of 0.4-1.5cm 3 / g.

[0022] The present invention also provides a modified silicon-carbon material prepared by the above-mentioned preparation method.

[0023] Optionally, the specific surface area of ​​the modified silicon-carbon material is 0.5-100 m 2 / g, D50 median particle size is 5-15μm, total pore volume ≤0.05cm 3 / g, tap density is 0.5-1.2g / cm 3 ;

[0024] The mass content of silicon is 30%-60%; the mass content of carbon is 40%-70%;

[0025] The present invention also provides a modified silicon-carbon material prepared by the above-mentioned preparation method, wherein a Si-X bond or a Si-R bond exists in the surface passivation layer of the modified silicon-carbon material, and the R group and the X group are not H.

[0026] The present invention also provides an application of the modified silicon-carbon material in a lithium-ion battery.

[0027] In the present invention, the composition and preparation method of the lithium ion battery are conventional in the art and are not specifically limited herein.

[0028] Specifically, the preparation method of the modified silicon-carbon material in the present invention may include the following steps:

[0029] (1) Using silane as the silicon source and inert gas or hydrogen as the carrier gas, the reaction is carried out in a chemical vapor deposition furnace, and the reaction is carried out at a constant temperature of 500 to 1000°C for 1 to 100 hours to deposit nano-silicon inside and on the surface of the porous carbon pores to prepare silicon-carbon materials. The chemical vapor deposition furnace is a horizontal furnace or a vertical furnace.

[0030] (2) Using organic silicon that exists stably in the air as a passivating agent, it is decomposed and uniformly passivated on the surface of the silicon-carbon material particles and the pores through physical vapor deposition (PVD) or chemical vapor deposition (CVD), thereby changing the dangling bonds and molecular composition on the surface of the nanosilicon particles, and depositing a nanoscale passivation layer on the porous carbon surface to isolate the nanosilicon from contact with external oxidizing substances.

[0031] The PVD method includes but is not limited to vacuum evaporation, vacuum sputtering, vacuum ion beam and the like.

[0032] The specific steps of CVD passivation may be: the organosilicon is atomized and then introduced into a chemical vapor deposition furnace, the organosilicon begins to decompose under the action of temperature, and its decomposition products are evenly distributed in the reactor chamber and fully contact with the material, thereby achieving the purpose of passivation.

[0033] In the present invention, the atomization method includes but is not limited to: single-phase atomization (direct atomization, centrifugal atomization and rotary atomization) and medium atomization (pneumatic atomization and bubble atomization) and other methods.

[0034] PVD passivation: The surface of the material source (solid or liquid) can be physically vaporized into gaseous atoms, molecules or partially ionized into ions under vacuum conditions. Then, low-pressure gas (or plasma) is passed into the chemical vapor deposition furnace and fully contacts the material to achieve the purpose of passivation.

[0035] The reaction principle of the modified silicon-carbon raw material provided by the present invention is as follows:

[0036] The process of silane cracking to form nano-silicon is the process of breaking Si-H bonds and forming Si-Si bonds. However, in order to ensure that the deposited nano-silicon is amorphous silicon, the temperature used to prepare the silicon-carbon material is not high, so the formed nano-silicon particles still have Si-H bonds. The organosilicon passivator is introduced into the chemical vapor deposition furnace in a certain way. By increasing the temperature or other means to empower the passivator molecules, the passivator RSiX3 or R2SiX2 is transformed from a stable state at room temperature to an intermediate decomposition product X3-Si with high chemical reaction activity. + / X2-Si + R / X2-Si 2+ (R-group refers to a group that is relatively unreliable in bonding with silicon. When R and X are the same, R represents a detachable group.) X-Si may also be produced during the activation of RSiX3 or R2SiX2. 3+ / Si 4+ Group, but X-Si 3+ / Si 4+ The group does not affect the formation of the passivation layer because activation will first produce X3-Si + / X2-Si + R / X2-Si 2+ groups, and control the activation degree and reaction temperature to minimize X-Si 3+ / Si 4+ The formation of the group; and X3-Si + / X2-Si + R / X2-Si 2+ The group is more likely to combine with Si-H, but X-Si 3+ / Si4+ It needs to react with multiple Si-H bonds to be stable. The intermediate decomposition product X3-Si + / X2-Si + R / X2-Si 2+ Reacts with the Si-H on the surface of the nano-silicon hydrogen termination, hydrogen combines with the R-group, and the intermediate decomposition product X2-Si + R / X3-Si + / X2-Si 2+ Replacing hydrogen to form Si-SiX2R, Si-Si-X3 or Si2-Si-X2 bonds, thereby changing the dangling bonds and molecular composition on the surface of the silicon-carbon material particles and forming a stable surface structure.

[0037] Directed deposition principle: using the intermediate decomposition product X2-Si + R / X3-Si + / X2-Si 2+ The performance difference between combining with silicon and combining with carbon is that the deposition of silicon on silicon is homogeneous deposition. Nano-silicon will provide "nucleation points" for the intermediate decomposition products before carbon, and Si-SiX2R, Si-Si-X3 or Si2-Si-X2 bonds will grow from these "nucleation points". At the same time, the surface of the porous carbon that has been heat-treated has fewer free groups, which can react with the intermediate decomposition products X2-Si + R / X3-Si + / X2-Si 2+ The combined CH bond content is low, and the carbon-silicon bond is more difficult to form than the silicon-silicon bond. In addition, the formation of silicon-silicon bonds can be guaranteed to the greatest extent by controlling the process parameters of the reactor temperature, the concentration of the intermediate decomposition products in the reactor cavity, and the residence time, while reducing the formation of silicon-carbon bonds. Therefore, it is possible to achieve the directionality of passivating the surface of the nano-silicon without reacting with carbon to deposit on the surface of the silicon-carbon particles to form a coating, resulting in the deterioration of the electrical conductivity and ion conductivity of the porous carbon substrate.

[0038] The technical solution of the present invention has the following advantages:

[0039] The preparation method of the modified silicon-carbon material provided by the present invention comprises the following steps: S1, depositing nano-silicon on a porous carbon material to obtain a silicon-carbon material; S2, passivating the obtained silicon-carbon material by physical vapor deposition or chemical vapor deposition, wherein the passivator used in the passivation process is an organic silicon passivator, wherein the general formula of the organic silicon passivator is RSiX3 or R2SiX2, and the R group and the X group are not H at the same time. The present invention uses a porous carbon material with a certain pore structure as a substrate, and deposits nano-silicon in situ inside the porous carbon to prepare a new silicon-carbon material, and passivates and modifies the surface of the silicon-carbon material by a silicon-containing substance, changes the dangling bonds and molecular composition of the surface of the silicon-carbon material particles, thereby obtaining a modified silicon-carbon material that can stably exist in air and slurry systems and has excellent processing performance, and the material has excellent electrochemical performance. The method can directionally passivate the surface of nano-silicon particles without further reacting with the silicon atoms inside the particles, because the X group carried by the intermediate decomposition product is difficult to diffuse between the silicon lattices. In the prior art, the oxidant not only reacts with the surface of nano-silicon, but the formation of the oxide layer is a dynamic process. As the oxidation proceeds, the oxide layer will gradually thicken. The stable Si-SiX2R, Si-Si-X3 or Si2-Si-X2 bonds formed by the passivation of the nano-silicon surface will prevent the reaction of oxidizing molecules with silicon atoms, thereby forming a stable surface structure.

[0040] The preparation method of the modified silicon-carbon material provided by the present invention limits the boiling point and cracking temperature of the organosilicon passivator, so that the passivator is in liquid state at normal temperature and pressure, which is convenient for transportation, storage, use and metering; the limitation of boiling point ≤300°C is convenient for atomizing it by common means; the limitation of cracking temperature ≤700°C is convenient for energizing the passivator and converting it into an active intermediate decomposition product, and the low passivation temperature is convenient for maintaining a smaller grain size of nano-silicon in the silicon-carbon material.

[0041] The preparation method of the modified silicon-carbon material provided by the present invention specifically selects the organosilicon passivating agent, which are common or industrially used organosilicon, are easier to obtain and have lower costs; and have relatively low toxicity, which is conducive to large-scale use.

[0042] The preparation method of the modified silicon-carbon material provided by the present invention can ensure the formation of silicon-silicon bonds to the greatest extent and reduce the formation of silicon-carbon bonds by specifically limiting the specific operating parameters of the passivation treatment step. Therefore, the surface of the nano-silicon can be passivated in a direction without reacting with carbon to be deposited on the surface of the silicon-carbon particles to form a coating, thereby further improving the electrochemical properties of the material.

[0043] The modified silicon-carbon material provided by the present invention is applied to lithium-ion batteries. The Si-H bonds are replaced to form Si-SiX2R, Si-Si-X3 or Si2-Si-X2 bonds with low reactivity. During storage and transportation, they will not react with oxygen in the air to generate the electrochemically inert substance silicon dioxide, thereby ensuring the stability of the gram capacity of the silicon-carbon material. In the slurry system, the nano-silicon surface passivation film isolates the reaction between silicon and water, which is beneficial to the control and uniformity of the slurry coating process, and further can limit the gas generation of the negative electrode in the battery, which is beneficial to improving the battery cycle life and safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 It is a process flow chart of the preparation of the modified silicon-carbon material provided in the embodiment of the present invention. DETAILED DESCRIPTION

[0046] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0047] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0048] For the convenience of data comparison, in the following examples and comparative examples, the porous carbon materials used have a D50 median particle size of 7 μm and a specific surface area of ​​1600 m 2 / g, tap density is 0.34g / cm 3 The pore volume is 0.93cm 3 / g

[0049] Example 1

[0050] This embodiment provides a modified silicon-carbon material, and its preparation process is as follows: Figure 1 As shown, the specific preparation method is as follows:

[0051] (1) Deposition of nano-silicon in porous carbon is a conventional process. Weigh 1 kg of porous carbon into the reactor, purge oxygen, detect leaks, and then heat up. Use monosilane (SiH4) as the silicon source, hydrogen as the carrier gas, the silicon source flow rate is 1 L / min, the carrier gas flow rate is 2 L / min, and argon is the carrier gas. A mixed gas with a flow rate of 3 L / min is introduced, and the reaction temperature is 500 ° C in a chemical vapor deposition furnace for 10 hours to deposit nano-silicon into the porous carbon pores and surface to prepare silicon-carbon materials. The chemical vapor deposition furnace is a horizontal rotary furnace.

[0052] (2) Organic silicon that exists stably in the air is used as a passivator (tetraethoxysilane is selected in this embodiment), and is decomposed and uniformly passivated on the surface of the silicon-carbon material particles and the pores by chemical vapor deposition (CVD), changing the dangling bonds and molecular composition on the surface of the nano-silicon particles, and depositing a nano-level passivation layer on the porous carbon surface to isolate the nano-silicon from contact with external oxidizing substances. The specific operation is as follows: the passivator is introduced into the atomizing device through a metering pump for atomization and then introduced into the reactor. The temperature of the passivation treatment is 400°C. The flow rate of the passivator entering the atomizer is controlled by the metering pump, so that the concentration of the organic silicon passivator in the reactor is controlled to be 0.5 mol / L, and the residence time is 1 hour.

[0053] Example 2

[0054] This embodiment provides a modified silicon-carbon material. Compared with Embodiment 1, the only difference is that the reaction temperature for depositing nano-silicon in step (1) is 600° C. and the deposition time is 10 h.

[0055] Example 3

[0056] This embodiment provides a modified silicon-carbon material. Compared with Embodiment 1, the only difference is that the reaction temperature for depositing nano-silicon in step (1) is 1000° C. and the deposition time is 2 h.

[0057] Example 4

[0058] This embodiment provides a modified silicon-carbon material. Compared with Embodiment 1, the only difference is that in step (2), the passivating agent is different, and in this embodiment, it is tetramethyl silicate.

[0059] Example 5

[0060] This embodiment provides a modified silicon-carbon material. Compared with Embodiment 1, the only difference is that in step (2), the passivating agent is selected differently, and in this embodiment, it is vinyl silane.

[0061] Example 6

[0062] This embodiment provides a modified silicon-carbon material. Compared with Embodiment 1, the only difference is that in step (2), the passivating agent is different, and in this embodiment, it is allyloxytrimethylsilane.

[0063] Example 7

[0064] This embodiment provides a modified silicon-carbon material. Compared with Embodiment 1, the only difference is that in step (2), the passivating agent is selected differently, and in this embodiment, it is methyltrichlorosilane.

[0065] Example 8

[0066] This embodiment provides a modified silicon-carbon material. Compared with Embodiment 1, the only difference is that in step (2), the temperature of the passivation treatment is 200° C., the concentration of the organosilicon passivator in the reactor is 1 mol / L, and the residence time is 0.5 h.

[0067] Example 9

[0068] This embodiment provides a modified silicon-carbon material. Compared with Embodiment 1, the only difference is that in step (2), the temperature of the passivation treatment is 800° C., the concentration of the organosilicon passivator in the reactor is 0.01 mol / L, and the residence time is 5 h.

[0069] Comparative Example 1

[0070] This comparative example provides a modified silicon-carbon material, which is different from Example 1 only in that the passivation treatment step (2) is not included.

[0071] Comparative Example 2

[0072] This comparative example provides a modified silicon-carbon material, which is different from Example 1 only in that: in step (2), a mixed gas of oxygen and nitrogen is used instead of an organic silicon passivating agent;

[0073] The specific operation of step (2) is: introducing a mixed gas of oxygen and nitrogen (wherein the volume ratio of oxygen to nitrogen is 1:4) into the reactor at a flow rate of 1 L / min, the temperature of the passivation treatment is 400° C., and the treatment time is 1 h.

[0074] The oxidant not only reacts with the surface of nano-silicon, but the formation of the oxide layer is a dynamic process. As the oxidation proceeds, the oxide layer will gradually thicken, causing the electrochemically inert silicon dioxide layer to gradually thicken, reducing the gram capacity of the silicon-carbon material. The thick oxide layer hinders the transmission of lithium ions and reduces the capacity of nano-silicon. At the same time, the sample will continue to react with oxygen in the air after oxygen treatment. The passivation agent treatment can directionally passivate the surface of nano-silicon particles without further reacting with the silicon atoms inside the particles. This is because the X group carried by the intermediate decomposition product is difficult to diffuse between the silicon lattices. The stable Si-Si-X3 or Si2-Si-X2 bonds formed by the passivation of the nano-silicon surface will prevent the reaction of oxidizing molecules with silicon atoms, thereby forming a stable surface structure.

[0075] Comparative Example 3

[0076] This comparative example provides a modified silicon-carbon material. Compared with Example 1, the only difference is that: step (2) uses a carbon source for coating. The specific operation is: after nano-silicon is deposited inside the porous carbon using a conventional process, acetylene is used as the carbon source and argon is used as the carrier gas. The coating is subjected to vapor phase carbon coating in a chemical vapor deposition furnace at a temperature of 700°C and a time of 8 hours to obtain a silicon-carbon composite negative electrode material.

[0077] Test Case

[0078] 1. Physical and chemical parameter test

[0079] The modified silicon-carbon materials obtained in each embodiment and comparative example were tested for physical and chemical parameters, and the specific surface area was tested by the GB / T19587 method, the D50 was tested by the GB / T 24533-2019 method, the total pore volume was tested by the GB / T7702.20-2008 method, the tap density was tested by the GB / 5162-85 method, and the carbon content was tested by the GB / T3521 method. The specific test results are shown in the following table:

[0080] Table 1

[0081]

[0082]

[0083] 2. Electrochemical performance test

[0084] The modified silicon-carbon materials obtained in each embodiment and comparative example were subjected to electrochemical performance tests, and the specific test method was as follows:

[0085] Gas production and viscosity test: The modified silicon-carbon material and binder solution (1.5% CMC) obtained in each embodiment and comparative example were weighed at a mass ratio of 1:3 and slurried with a beater. Then, part of the slurry was put into an aluminum-plastic film bag, which was evacuated and sealed. The volume change, i.e., the gas production, was measured by the Archimedes drainage method at 45°C in a constant temperature box; the slurry was put into a sealed can, stored at room temperature 25°C for different time periods, and its viscosity was tested using a viscosity tester.

[0086] Powder resistivity: The test method is based on the GB / T24521-2018 standard.

[0087] Battery assembly method: The modified silicon-carbon material obtained in each embodiment and comparative example, the conductive additive carbon black, and the adhesive (sodium carboxycellulose and styrene-butadiene rubber in a mass ratio of 1:1, the same below) are weighed according to a mass ratio of 94%:2%:4%, and the slurry is prepared with a beater, and a 250μm scraper is used to coat the coating machine at 30mm / s, and baked at 80℃ for 2h. Celgard2400 model polypropylene diaphragm is used, metal lithium sheet is selected as the positive electrode, and LiPF6 system electrolyte [LiPF6 solution with a concentration of 1 mol / L, EC / DC 1:1 (volume ratio) mixed solution as solvent] is used as the electrolyte, and CR2032 button batteries are assembled in a glove box. A charge and discharge instrument is used for constant current charge and discharge test, the discharge cut-off voltage is 0.005V, the charge cut-off voltage is 2V, and the first week of charge and discharge test is carried out at a current density of 1C / 10. Thus, the material charge and discharge capacity and the first coulomb efficiency are obtained.

[0088] Fully electric test method:

[0089] All-electric preparation method: Preparation of negative electrode sheet: The modified silicon-carbon material obtained in each embodiment and comparative example is configured with graphite to form a composite with a specific capacity of 450mAg / h, and a slurry is prepared with a conductive additive carbon black and a binder in a ratio of 94%:2%:4%, and the slurry is coated on the collector to obtain a negative electrode sheet; the active material LiCoO2, conductive carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-pyrrolidone solvent system in a weight ratio of 96.7:1.7:1.6, and then coated on Al foil, dried, and cold pressed to obtain a positive electrode sheet; a PE porous polymer film is used as an isolation film, and the above-mentioned positive electrode sheet, isolation film, and negative electrode sheet are stacked in order, so that the isolation film is between the positive electrode sheet and the negative electrode sheet to play an isolation role, and then wound to obtain a bare battery cell. Place the bare cell in the outer packaging and inject the prepared electrolyte (404865 cell (positive electrode surface density 17.9g / cm 2 , negative electrode 7.0g / cm 2The electrolyte used was Xinzhoubang LBC421B10) and packaged, and the full battery cell was obtained through the process of formation, degassing, and trimming. The constant current charge and discharge test was carried out using a charge and discharge instrument, with a discharge cut-off voltage of 2.75V and a charge cut-off voltage of 4.2V. The charge and discharge tests were all carried out at a current density of 1C, and the capacity retention rate of 100 cycles of full power was tested.

[0090] The specific test results are shown in the table below:

[0091] Table 2

[0092]

[0093] From the data in the above table, it can be seen that the gas production per gram of active substance in 48 hours of the modified silicon-carbon material treated with a passivator in the slurry system is significantly lower than that of other treatment methods. This proves that the passivation coating effectively isolates the nano-silicon from contact with the slurry and effectively inhibits the gas production; the untreated sample nano-silicon in Example 1 has many active Si-H bonds on the surface and strong reaction activity, which reacts with water in the slurry system to produce a large amount of gas; although the coating layer formed by oxygen passivation in Example 2 and carbon coating in Example 3 can isolate the nano-silicon from contact with water to a certain extent, it is difficult to completely isolate it and gas will still be produced.

[0094] The small viscosity change rate of the passivation coated sample indicates that the silicon-carbon material is stable in the solution and the degree of reaction between nano-silicon and water is low, which shows that the passivation coating effectively improves the processing performance; while the sample in comparative example 1 not only reacts violently with water, but also because the formed silica layer is hydrophobic, it will continuously react and sink to the bottom during the standing process, resulting in a large rate of change of the surface viscosity; the sample in comparative example 2 shows that the silica layer is hydrophobic, and it sinks to the bottom after standing, resulting in a large rate of change of the surface viscosity; in comparative example 3, since the carbon layer is formed at low temperature, it will have obvious hydrophobicity and cause it to sink to the bottom.

[0095] The powder resistivity, capacity and initial efficiency prove that no coating will be formed on the surface of silicon-carbon particles, which will not lead to the deterioration of the electrical conductivity and ion conductivity of silicon-carbon materials. At the same time, the capacity retention rate after 100 cycles of full power can show that passivation treatment can also effectively improve the cycle performance of silicon-carbon materials.

[0096] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a modified silicon-carbon material, characterized in that: The steps include: S1, depositing nano-silicon on a porous carbon material to obtain a silicon-carbon material, wherein the nano-silicon is amorphous silicon and Si-H bonds exist on the surface of the nano-silicon particles; S2, passivating the obtained silicon-carbon material by physical vapor deposition or chemical vapor deposition, wherein the passivating agent used in the passivation process is an organic silicon passivating agent, The general formula of the organosilicon passivator is RSiX3 or R2SiX2, and the R group and the X group are not H at the same time.

2. The method for preparing the modified silicon-carbon material according to claim 1, characterized in that: The organosilicon passivator is in liquid state at normal temperature and pressure, with a boiling point of ≤300°C and a cracking temperature of ≤700°C.

3. The method for preparing the modified silicon-carbon material according to claim 2, characterized in that: In the organosilicon passivator, the R group and the X group are independently selected from at least one of hydrogen, halogen, hydroxyl, alkyl, alkenyl, alkoxy, phenyl, and alkylamine; Optionally, the R group and the X group are independently selected from at least one of -H, -Br, CI, -OH, -Cl, -CCH, -CH3, -C2H4, -OCH3, -OC2H6, -C6H5, -OC3H5, and -C3H8N.

4. The method for preparing the modified silicon-carbon material according to claim 3, characterized in that: The organic silicon passivating agent includes at least one of tetraethoxysilane, tetramethyl silicate, methyltrichlorosilane, r-aminopropyltriethoxysilane, vinyl silane, and allyloxytrimethylsilane.

5. The method for preparing the modified silicon-carbon material according to any one of claims 1 to 4, characterized in that: In step S2, the temperature of the passivation treatment is 100-800°C, the concentration of the organosilicon passivator in the reactor is 0.01-1 mol / L, and the residence time is 0.1h to 5h; Optionally, the temperature of the passivation treatment is 200-700°C.

6. The method for preparing the modified silicon-carbon material according to claim 5, characterized in that: In step S2, the physical vapor deposition is selected from one of vacuum evaporation, vacuum sputtering, and vacuum ion beam method; And / or, in the chemical vapor deposition method, the organosilicon passivator is pre-atomized.

7. The method for preparing the modified silicon-carbon material according to any one of claims 1 to 4, characterized in that: In step S1, silane is used as a silicon source and nano-silicon is deposited by chemical vapor deposition; And / or, the temperature of the nano-silicon deposition step is 500-1000° C., and the reaction time is 1-100 h; and / or, using an inert gas or hydrogen as a carrier gas; And / or, the porous carbon material has a D50 median particle size of 6-20 μm and a specific surface area of ​​500-2000 m 2 / g, tap density is 0.2-0.6g / cm 3 The pore volume is in the range of 0.4-1.5cm 3 / g.

8. A modified silicon-carbon material prepared by the preparation method according to any one of claims 1 to 7, wherein a Si-X bond or a Si-R bond exists in the surface passivation layer of the modified silicon-carbon material, and the R group and the X group are not H.

9. The modified silicon-carbon material according to claim 8, characterized in that: The specific surface area of ​​the modified silicon-carbon material is 0.5-100 m 2 / g, D50 median particle size is 5-15μm, total pore volume ≤0.05cm 3 / g, tap density is 0.5-1.2g / cm 3 ; The mass content of silicon element is 30%-60%; the mass content of carbon element is 40%-70%.

10. Use of the modified silicon-carbon material according to claim 8 or 9 in a lithium-ion battery.

Citation Information

Patent Citations

  • Composite material, preparation method and application thereof, electrode and lithium ion battery

    CN110752364A

  • Silicon-carbon negative electrode material, preparation method thereof and lithium ion battery

    CN115458715A

  • Additive for lithium ion battery, lithium ion battery and electric equipment

    CN115863764A

  • Lithium ion battery silicon-carbon negative electrode material and preparation method and application thereof

    CN116169255A

  • Graphene passivation solution, preparation method thereof, lithium battery soft package aluminum plastic film and lithium battery

    CN116179031A